2007
DOI: 10.1016/j.jsv.2006.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Active control of sound inside a sphere via control of the acoustic pressure at the boundary surface

Abstract: Here we investigate the practical feasibility of performing soundfield reproduction throughout a three-dimensional area by controlling the acoustic pressure measured at the boundary surface of the volume in question. The main aim is to obtain quantitative data showing what performances a practical implementation of this strategy is likely to yield. In particular, the influence of two main limitations is studied, namely the spatial aliasing and the resonance problems occurring at the eigenfrequencies associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Other methods have been proposed, whose formulation includes the Kirchhoff-Helmholtz equation and the theory of inverse problems and acoustic holography (see, for example, [Ise99] and [CIB08] [VW04]) and active control of sound [NE92], [EF07]. All the techniques mentioned above have in common the fact that, from the knowledge of a portion of a given sound field, they aim at solving a similar mathematical inverse problem, in order to either reconstruct the acoustic pressure and particle velocity fields near the source (acoustic holography), to identify the sources of sound generating a given field (source reconstruction) or to define the signals driving an array of secondary sources for canceling sound (active noise control) or synthesizing a given sound field (sound field reproduction).…”
Section: Other Methods For Sound Field Reproductionmentioning
confidence: 99%
“…Other methods have been proposed, whose formulation includes the Kirchhoff-Helmholtz equation and the theory of inverse problems and acoustic holography (see, for example, [Ise99] and [CIB08] [VW04]) and active control of sound [NE92], [EF07]. All the techniques mentioned above have in common the fact that, from the knowledge of a portion of a given sound field, they aim at solving a similar mathematical inverse problem, in order to either reconstruct the acoustic pressure and particle velocity fields near the source (acoustic holography), to identify the sources of sound generating a given field (source reconstruction) or to define the signals driving an array of secondary sources for canceling sound (active noise control) or synthesizing a given sound field (sound field reproduction).…”
Section: Other Methods For Sound Field Reproductionmentioning
confidence: 99%
“…To determine the spatial placement of the loudspeaker aperture function, we need to find an appropriate radius and elevation angle. Consider (19), in order to calculate β N (kr q ) and Legendre functions properties P N N (cos θ q ) for this circle. From Figure 2, we observe that there are certain elevation angles where the magnitude of the field is quite low or zero.…”
Section: A Location Of Circles Using Mode Selectionmentioning
confidence: 99%
“…We also set β N (k) = 0 for all other circles q = 2 · · · Q, which we will add to the system in the subsequent steps. Thus, (19) reduces to …”
Section: A Location Of Circles Using Mode Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, only a few studies that validate sound field control with loudspeakers experimentally have been published. [10][11][12][13][14][15] These studies have shown that the sound field control is feasible as expected from the simulations, but the exterior region of the loudspeakers array has not been considered.…”
mentioning
confidence: 99%